INTENSITAS PERNIKAHAN DINI DAN PERCERAIAN DINI DI DESA ROWOGEMPOL KECAMATAN LEKOK KABUPATEN PASURUAN TAHUN 2022-2023 - Sulihiyah; Fida , Imanuddin Abil (LPPM STAI Muhammadiyah Probolinggo, 2023)
Marriage is crucial for fulfilling human biological needs. Often, couples opt for early marriage, which unfortunately may end in early divorce. In Indonesia, these cases are not uncommon, with an increase observed in 2023 compared to previous years. The quality of children, family, family harmony, and divorce are all influenced by these issues, leading to school dropout rates. In Desa Rowogempol, Kecamatan Lekok, Kabupaten Pasuruan, early marriages are prevalent despite the enactment of Law No. 16 of 2019, which sets the minimum marriage age at 19 for both genders. This context sets the basis for this study, aiming to understand the intensity, factors, and impacts of early marriage and divorce in Desa Rowogempol. The research employs qualitative methods (field research). Quantitative data on early marriages are collected from the Office of Religious Affairs (KUA) in Kecamatan Lekok, while data on divorces resulting from early marriage are obtained from the Religious Court (PA) in Kabupaten Pasuruan. Qualitative data are gathered through face-to-face interviews and online media with relevant parties. The study reveals an increase in early marriage intensity from 2022-2023, while early divorce shows a decline. Generally, early marriages occur due to arranged marriages or inappropriate social interactions, often leading to early divorces due to frequent conflicts stemming from the arranged nature of the marriage. keywords: Early Marriage, Early Divorce, Intensity of Marriage and Divorce